Antibacterial activity of cinnamon (Cinnamomum zeylanicum) essential oil and cinnamaldehyde against fish pathogenic bacteria isolated from cultured olive flounder Paralichthys olivaceus - Pathirana, H. N. K. S.; Wimalasena, S. H. M. P.; De Silva, B. C. J.; Hossain, S.; Heo, G. J. (Indian Journal of Fisheries, 2019)
Antibacterial activity of cinnamon (Cinnamomum zeylanicum) essential oil (CEO) and cinnamaldehyde was tested against seven Gram negative and nine Gram positive fish pathogenic bacteria isolated from cultured olive flounder (Paralichthys olivaceus) in Korea. Disk diffusion assay, MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) tests were done. Cinnamon and cinnamaldehyde inhibited the growth of both Gram negative and Gram positive bacteria. Cinnamaldehyde showed lower MIC values than CEO which ranged from 0.001 to 0.015% (V/V). CEO (MBC/MIC 2-4) was bactericidal for all tested strains while cinnamaldehyde was bactericidal for all except 6 strains. For all fish pathogenic bacteria, the inhibition zone diameter (IZD) increased in proportion to the oil concentration and the maximum effect was found at 100% (V/V) concentration of CEO and cinnamaldehyde. Â The antibiogram pattern indicated that all the bacterial strains excluding three strains of Streptococcus iniae (S186, S530 and S131) showed resistance to one or more antibiotics. Higher percentages of relative inhibition zone diameter (RIZD %) were exhibited at higher concentrations of CEO and cinnamaldehyde. Since antibacterial activities of CEO and cinnamaldehyde were considerably effective against fish pathogenic bacteria, these could be used as alternatives to treat bacterial infections in aquaculture.Keywords: Antibacterial activity, Cinnamon essential oil, Cinnamaldehyde, Fish pathogenic bacteria, Olive flounder